Effect of thread shape on screw stress concentration by photoelastic measurements - Dragoni E. (Publ by ASME, 1993)
The screw stress concentration for six nut-bolt connections embodying three different thread profiles and two nut shapes is measured photoelastically. Saw-toothed (nearly zero flank angle), trapezoidal (15-degree flank angle) and triangular (30-degree flank angle) thread forms are examined in combination with standard and lip-type nuts. The effect of the thread profile on the screw stress concentration appears to be dependent upon the kind of nut considered. If the fastening incorporates a standard nut, the saw-toothed thread is stronger than the triangular one which, in turn, behaves better than the trapezoidal contour. The improvement is roughly a 20 per cent reduction in the stress concentration factor from the trapezoidal to the saw-toothed thread. In the case of lip nut, conversely, this tendency is somewhat reversed, with the trapezoidal thread performing slightly (but not decidedly) better than the other two shapes. Finally, averaged over all three thread forms, the lip nut exhibits a stress concentration factor which is about 50 per cent lower than the standard nut's.